ON THE POSSIBLE TRIPLICITY OF THE BINARY SYSTEM UU SAGITTAE - Bezdenezhnyi, V. P. (Одеські астрономічні публікації, 2017)
On the basis of the photographic observations of the Algol-type eclipsing variable UU Sge has been revealed the light-time effect in the 0-C diagram. Probably, it has been evoked by the third close (1.6 AU) invisible companion.